Synthesis of steroidal quinones and hydroquinones from bile acids by Barton radical decarboxylation and benzoquinone addition: Studies on their cytotoxic and antifungal activities - Siless, Gastón Ezequiel (2012)
Twelve new hydroquinones and quinones (4a-c to 7a-c) derived from free or peracetylated bile acids were prepared by a Barton decarboxylation reaction, with subsequent trapping of the resulting free radical by benzoquinone. All new compounds were completely characterized by 2D NMR techniques and screened for antifungal and cytotoxic activity. One of the new hydroquinones (7b) showed promising results against the human pancreatic ductal carcinoma cell line PANC1, with similar cytotoxic activity as the commercial chemotherapy drug doxorubicin.